Biosynthesis, in vivo and in vitro depolymerizations of intracellular medium chain length poly-3 hydroxyalkanoates / Siti Nor Syairah Anis - Siti Nor Syairah , Anis (2017)
Medium chain length poly-3-hydroxyalkanoates (mcl-PHA) is a biodegradable polymer made of different hydroxyalkanoates with (R)-configuration as monomeric units and a source of valuable biomaterials. Biosynthesis, in vivo and in vitro depolymerization of intracellular mcl-PHA in Pseudomonas putida Bet001 grown on lauric acid was studied. Highest mcl-PHA fraction (> 50 % of total biomass) and cell concentration (8 g L-1) were obtained at carbon-to-nitrogen (C/N) ratio 20, initial cell concentration 1 g L-1, and 48 hours fermentation. The mcl-PHA comprised of 3-hydroxyhexanoate (C6) (6.1 ± 2.0 mol%), 3-hydroxyoctanote (C8) (40.1 ± 2.7 mol%), 3-hydroxydecanoate (C10) (32.8 ± 2.8 mol%) and 3-hydroxydodecanoate (C12) (21.0 ± 3.2 mol%). In vivo action was studied in a mineral liquid medium without carbon source, and in different buffer solutions with varied pH, molarity, ionic strength (I) and temperature. Rate and percentage of in vivo depolymerization were highest in 0.2 M Tris-HCl buffer (pH 9, I = 0.2 M, 30 ºC) at 0.21 g L-1 h-1 and 98.6 ± 1.3 wt%, respectively. There is a congruity visà- vis to specific buffer type, molarity, pH, I and temperature values for superior in vivo depolymerization activities. For in vitro depolymerization studies, cell-free system was obtained from lysing bacterial cells suspension by ultrasonication at optimum conditions (frequency 37 kHz, 30 % of power output, < 25 ºC for 120 minutes). The comparison between in vivo and in vitro depolymerizations of intracellular mcl-PHA was made. In vitro depolymerization showed lower depolymerization rates and activities compared to in vivo depolymerization. However, final product yield of in vitro depolymerization showed higher yield compared to in vivo depolymerization. The monomer liberation rate reflected the mol% distribution of the initial polymer subunit composition, and the resulting direct individual products of depolymerization were identical for both in vivo and in vitro processes. It points to exo-type reaction for both processes, and potential biological route to chiral molecules.